The ageing immune system - Djukic, M.; Nau, R.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2014)
The aging of the immune system, also called immunosenescence, contributes to the increased morbidity and mortality from infections, autoimmune diseases and cancer as well as to the low efficacy of vaccination in elderly persons. Immunosenescence is characterized by a decrease in cell-mediated immune function and by reduced humoral immune responses caused by age-related changes in the innate immune system and age-dependent defects in T-and B-cell function. This paper gives an overview of the most important modifications in the different compartments of the immune system during the ageing process.
EVALuna2:10521